Does the vitamin C level affect postoperative analgesia in patients who undergo orthognathic surgery? - Süzen, Muazzez; Zengin, Mustafa; Çiftçi, Bahadır; Uçkan, Sina (Churchill Livingstone, 2023)
Vitamin C has a critical role in pain management because of its antioxidative, neuroprotective, and anti-nociceptive properties. Oxidative stress caused by surgery increases the requirement for vitamin C. The aim of this study was to evaluate the change in vitamin C level and its effect on postoperative pain in patients undergoing orthognathic surgery. Thirty patients were included in the study. The relationships between the postoperative plasma vitamin C level, duration of surgery, postoperative analgesic consumption, and pain scores (visual analogue scale) were analysed. The difference between the mean pre-and postoperative vitamin C levels was found to be statistically significant (7.5 +/- 2.9 mg/l vs 4.9 +/- 2.3 mg/l, respectively; P = 0.001). There was no significant relationship between the duration of surgery and the vitamin C level decrease (P > 0.05). There was an inverse correlation between the postoperative vitamin C level and the amount of analgesic requested via patient-controlled analgesia (r = -0.699, P < 0.001). The findings suggest that, in patients who undergo orthognathic surgery, plasma vitamin C levels decrease significantly (34.6%), and an increase in the duration of surgery is not associated with any decrease in the vitamin C levels. A low postoperative plasma vitamin C level was found to be associated with greater postoperative analgesic consumption. In patients with preoperative plasma vitamin C levels <= 42 mu mol/l, perioperative vitamin C administration may be considered for postoperative pain management.
Keywords: Orthognathic Surgery; Vitamin C; Oxidative Stress; Postoperative Pain; Analgesia